Strategi Internalisasi Nilai-Nilai Agama Islam kepada Masyarakat melalui Pengajian Jum’at di Kraksaan Probolinggo - Muhammad Munif (GUYUB: Journal of Community Engagement, 2020)
People in Kraksaan City, Probolinggo District are religious. In their daily religious activities, they use the great mosque of Ar-Raudlah as a place of religious worship. This mosque is a place where they pray for five times, recite Qoran, contemplate silently (i’tikaf), and involve with religious recitation. A morning class (kuliah shubuh) at Ar-Raudlah is possibly transforming people’s mindset and behavior into more religious, since some of them act illegal lottery and money laundry. By implementing internalisation of religious values with talking (qoulan) technique, they are being regretful, aware of their sins, abandoning these forbidden behaviors, and reinforcing their understanding of Islam. Beside of kuliah shubuh, there are a new program namely interpretation of Koran to increase their understanding of Koran.Keywords: Jum’at recitation, Kraksaan people, internalisastion of Islamic values, masjid Ar Raudlah